Perspectives on International Exchanges and International Circulation of Ideas and Urban Models (Andamios, Revista de Investigación Social, 2013)
This paper seeks to emphasize the relevance of analyzing the exchanges between local and foreign counterparts. Latin American cultural history, cultural studies as well as architecture and urbanism histories contribute to discuss dependentists analyses on center –periphery relations. Those research lines enable a more productive approach on international circulation of ideas, technicians and urban models as well as international exchanges. The theoretical approach is articulated with a previous research that analyzes the struggle to define diagnoses of Buenos Aires city problems between 1983 and 1992. Those diagnosis are developed by various networks of local professional and technician, related in multiple ways with Spanish peer
Keywords: Theoretical Approaches; International Exchanges; Circulation of Urban Ideas; Networks of Professional and Technicians